Characterization of three Ixodes scapularis cDNAs protective against tick infestations - Almazán, Consuelo (2005)
cDNA expression library immunization (ELI) and analysis of expressed sequenced tags (EST) in a mouse model of tick infestations was used to identified cDNA clones that affected I. scapularis. Three protective antigens against larval tick infestations, 4F8, with homology to a nucleotidase, and 4D8 and 4E6 of unknown function, were selected for further characterization. All three antigens were expressed in all I. scapularis stages and localized in adult tick tissues. 4D8 was shown to be conserved in six other tick species. Based on immunization trials with synthetic polypeptides against larvae and nymphs and on artificial feeding experiments of adults, these antigens, especially 4D8, appear to be good candidates for continued development of a vaccine for control of tick infestations and may be useful in a formulation to target multiple species of ticks.